A Study of Macao Tertiary Students' Attitudes Towards Language After the Handover - Yan, Xi. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on the attitudes of Macao tertiary students toward language after the handover. It shares the findings of a questionnaire survey and semi-structured interviews, which were conducted among freshmen of the University of Macao to investigate their attitudes toward Cantonese, Putonghua, English, and Portuguese, as well as their attitudes toward Macao's language planning and language policy. Utilizing a multidimensional and multilayered perspective in the study, this book also demonstrates the orientations of Macao tertiary students and the correlation between their social categories (gender and social class) and their attitudes toward language.
Chapter 1 Introduction -- Chapter 2 Literature Review -- Chapter 3 The Language Situation in Macao -- Chapter 4 Research Design -- Chapter 5 Questionnaire Survey Results -- Chapter 6 Interview Results -- Chapter 7 Discussion -- Chapter 8 Conclusions.
Keywords: Language and languages -- Study and teaching; Educational sociology; Education and state; Language Teaching and Learning; Sociology of Education; Educational Policy and Politics